PENGABDIAN MASYARAKAT MELALUI KULIAH KERJA NYATA : PENERAPAN LITERASI DAN NUMERASI MELALUI KEGIATAN POJOK BACA CERIA DI SD NEGRI 3 SADAPAINGAN - Fiky Siti Fadillah; Heti Triwhyuni; Syaharani Putri Salsabila; Nindia Agustin Azzahra; Sindi Aprilia; Hilma Anisyadi'ah; Rio Adistian; nadia ayu pratiwi; viki rizki; Tri Asih; Fauzan Zainal abidin; fauzi zainal abidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Basic education plays a crucial role in building the foundation of students’ literacy and numeracy skills. However, various reports indicate that literacy and numeracy levels in Indonesia remain relatively low, as reflected in UNESCO data and the PISA assessment results. This condition is also evident at SD Negeri 3 Sadapaingan, where both reading materials and numeracy media are still limited. To address this challenge, the Pojok Baca Ceria (Joyful Reading Corner) program was implemented through a Community Service Program (KKN) as an effort to foster a reading culture and improve students’ basic arithmetic skills. This study employed a community-based approach with several stages, including survey, socialization, implementation, evaluation, and documentation. The target group consisted of grade I–IV students, with the program being carried out over two weeks, two sessions per week. The results revealed a highly positive response from students since the beginning of the implementation. Lower-grade students were enthusiastic about reading illustrated storybooks and were able to retell the content, while upper-grade students showed interest in solving numeracy problems derived from reading texts. The presence of a well-decorated reading corner equipped with diverse learning materials successfully motivated students to engage in reading and practicing numeracy. Moreover, some students gradually developed the habit of reading independently outside the scheduled sessions. These findings are consistent with previous studies that highlight the effectiveness of reading corners in enhancing students’ motivation, independence, as well as literacy and numeracy skills. In conclusion, the Pojok Baca Ceria program at SD Negeri 3 Sadapaingan effectively improved students’ literacy and numeracy abilities while creating a creative and enjoyable learning atmosphere. This program is recommended to be developed further with the support of teachers, schools, and parents to ensure sustainability.